Permasalahan Sampah di Tiban Lama dan Cara Mengatasinya - Nainggolan, Pebrianto; Stella, Milenia; Dewantari, Desy Anti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Community service activities (SEPORA) aim to (1) Generate a sense of awareness from every resident of Sekupang District, Tiban Lama District, Rt01 / Rw01 in disposing garbage neatly (2) Increasing knowledge of Sekupang District residents, Tiban Lama District, Rt01 / Rw01 about sorting out garbage properly and (3) Help facilitate the work of TPS3R in making compost. Achieving these goals is done through socialization, with the method of exposure to concepts, questions and answers, and a direct approach. After the socialization activities were carried out, the implementation team participated in a community program on cleanliness (mutual cooperation) and re-socialization (sticking stickers) to the houses while monitoring and evaluating the level of awareness of the local community. The results show that the SEPORA program is running well and smoothly. This program can increase knowledge and be able to create public awareness about proper waste separation. Constraints that arise vary greatly starting from the rejection of the community, do not want to know, and attitudes that are always blamed can be overcome by the method of direct approach, although not all can accept it. The suggestions and input that can be conveyed from the results of the SEPORA program, the community, and local leaders are expected to have motivation, enthusiasm and to always foster the right sorting activities. The government is expected to start participating in the settlement of existing waste in the community, providing land suitable for landfills and providing adequate BIN facilities. For LPM through TPS3R, the program must always persuade similar programs to continue to run and develop.